Treatment Precedes Positive Symptoms in North American Adolescent and Young Adult Clinical High Risk Cohort. Issue 1 (2nd January 2018) - Woodberry, Kristen A.; Seidman, Larry J.; Bryant, Caitlin; Addington, Jean; Bearden, Carrie E.; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; McGlashan, Thomas H.; Mathalon, Daniel H.; Perkins, Diana O.; Tsuang, Ming T.; et al.
Abstract : Early intervention for psychotic disorders, a growing international priority, typically targets help-seeking populations with emerging psychotic ("positive") symptoms. We assessed the nature of and degree to which treatment of individuals at high risk for psychosis preceded or followed the onset of positive symptoms. The North American Prodrome Longitudinal Study–2 collected psychosocial treatment histories for 745 (98%) of 764 high-risk participants ( M age = 18.9, 57% male, 57.5% Caucasian, 19.1% Hispanic) recruited from 8 North American communities. Similar to prior findings, 82% of participants reported psychosocial treatment prior to baseline assessment, albeit with significant variability across sites (71%–96%). Participants first received treatment a median of 1.7 years prior to the onset of a recognizable psychosis-risk syndrome. Only one fourth sought initial treatment in the year following syndrome onset. Although mean sample age differed significantly by site, age at initial treatment ( M  = 14.1, SD  = 5.0) did not. High rates of early treatment prior to syndrome onset make sense in light of known developmental precursors to psychotic disorders but are inconsistent with the low rates of treatment retrospectively reported by first-episode psychosis samples. Findings suggest that psychosis risk studies and clinics may need to more actively recruit and engage symptomatic but non-help-seeking individuals and that community clinicians be better trained to recognize both positive and nonspecific indicators of emerging psychosis. Improved treatments for nonspecific symptoms, as well as the characteristic attenuated positive symptoms, are needed.